Cervical dystonia: pain relieving effects of botulinum toxin treatment - Marciniec, Michał; Szczepańska-Szerej, Anna; Rejdak, Konrad (Journal of Education, Health and Sport, 2018)
Cervical dystonia (CD) is a third most common movement disorder characterized by sustained or intermittent muscle contractions causing abnormal movements and postures of head and neck. Physical, emotional, cognitive, and self-awareness aspects are also affected, so CD is currently considered to be a “network” disorder with the involvement of multiple brain regions and cellular mechanisms. Pain occurs in 54.6% to 88.9% of patients with CD and is the most disabling non-motor symptom which strongly attributes to the quality of life deterioration. The dystonia-related pain is also the main reason patients are looking for treatment. Despite the high prevalence only small number of studies develops this issue. Botulinum toxin (BoNT) is a safe, efficacious and first choice treatment for CD. Up to 90% of patients reports an improvement in pain and motor symptoms after BoNT injections, however above mentioned effects may be partially independent due to the earlier and longer pain relief compared to muscle relaxation. The results of current studies suggest analgesic effects of BoNT are related to not only the acting in the neuromuscular junction. The central processing of nociceptive stimuli is contributed to be the main effect of BoNT analgesic therapy. To date, evidence for the association between dystonia-related pain and BoNT treatment become more significant but is still lacking. Further research is needed to investigate above correlation and issue an unambiguous high-level recommendations of analgesic therapy in CD.